1998
DOI: 10.1093/brain/121.6.1143
|View full text |Cite
|
Sign up to set email alerts
|

Aversive gustatory stimulation activates limbic circuits in humans

Abstract: Animal studies implicate the amygdala and its connections in the recognition of aversive stimuli. A recent PET study demonstrated that the human amygdala and left orbitofrontal cortex show substantial increases in regional cerebral blood flow (rCBF) during exposure to aversive odourants. To examine if aversive gustatory stimuli similarly activate these regions, nine healthy women tasted an aversive saline solution, pure water and chocolate while rCBF was measured with PET. The aversive saline condition, when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
169
2
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(189 citation statements)
references
References 72 publications
16
169
2
2
Order By: Relevance
“…The link between drug craving and OFC activity is the most common association found in this type of functional imaging work, and has led to the hypothesis that the OFC mediates drive and compulsive behavior associated with drug dependence (Volkow and Fowler, 2000). This region is also thought to mediate decision making that leads to reward (London et al, 2000;O'Doherty et al, 2001a;Ernst et al, 2002) and to act as a secondary processing center for gustatory (Zald et al, 1998;O'Doherty et al, 2001b) and olfactory (Zatorre et al, 1992;Levy et al, 1997;Zald and Pardo, 1997) stimuli. These putative functions of the OFC may help explain the consistent positive association between metabolism in this region and craving.…”
Section: Discussionmentioning
confidence: 96%
“…The link between drug craving and OFC activity is the most common association found in this type of functional imaging work, and has led to the hypothesis that the OFC mediates drive and compulsive behavior associated with drug dependence (Volkow and Fowler, 2000). This region is also thought to mediate decision making that leads to reward (London et al, 2000;O'Doherty et al, 2001a;Ernst et al, 2002) and to act as a secondary processing center for gustatory (Zald et al, 1998;O'Doherty et al, 2001b) and olfactory (Zatorre et al, 1992;Levy et al, 1997;Zald and Pardo, 1997) stimuli. These putative functions of the OFC may help explain the consistent positive association between metabolism in this region and craving.…”
Section: Discussionmentioning
confidence: 96%
“…Further studies are needed to elucidate the role of the insula in motivationally modulated response to food-related stimuli. Increased responses in the ACC have been documented in response to aversive gustatory stimuli (Zald et al, 1998), anticipatory taste during hunger , and visual images of food during hunger . Our finding of increased activity in the anterior cingulate cortex in response to food stimuli during hunger is consistent with these reports and may be related to the monitoring of unpleasant internal sensations associated with hunger (Craig et al, 1996;Tataranni et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the hypothalamus in food motivation is well established in literature on non-human primates (Rolls et al, 1976) as well as humans (Rolls, 1981;Stellar, 1954). More recently, however, limbic-frontal connectivity has become increasingly implicated in normal food motivation (Zald et al, 1998), as well as abnormal food intake and obesity . Previous human and animal studies suggest coordinated involvement of these areas in processing of emotional stimuli and representation of reward (Baxter and Murray, 2002;Gottfried et al, 2003;Kringelbach and Rolls, 2004;Rolls, 2004;Whalen, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Taste processing in the human OFC Studies using positron emission tomography and functional MRI have identified numerous taste-related areas within the OFC Zald et al, 1998;Frank et al, 2003). Unlike the primary taste cortex, activation of these OFC areas is often dependent on either the affective valence of the stimulus (De Araujo et al, 2003;Small et al, 2003) or the subject's internal state, such as their level of hunger/satiety (Gautier et al, 2000;Del Parigi et al, 2002b) (but see LaBar et al, 2001;Del Parigi et al, 2002a).…”
Section: Discussionmentioning
confidence: 99%